Changes and lessons learned from Covid-19 and the territorial dimension of health: for a new generation of development public policies - Lastres, Helena M. M.; Apolinário, Valdênia; Castro, Sérgio; Matos, Marcelo (Cadernos do Desenvolvimento, 2023)
The paper analyses the set of revelations as- sociated to COVID-19 and what was learned from it and discusses the position of health as an axis of a new development project. Besides environmental and inequity issues, it also ex- amines processes and impasses related to the State’s role and public services; the new productivity and technological dynamics; and the systemic and contextualized view of production and development. Drawing on Celso Furtado’s work, which emphasizes the importance of a broad approach and considers the territory as a vital element in the analyses and propositions of policies, this study focuses on health and its production system and on how to ensure its quality and universal access.